Biomedical applications of magnetic particles - Anker, Jeffrey N.; Mefford, Thompson (O. Thompson) (Boca Raton, FL : CRC Press, 2021)
"Magnetic particles are increasingly being used in a wide variety of biomedical applications. Written by a team of internationally respected experts, this book provides an up-to-date authoritative reference for scientists and engineers. The first section presents the fundamentals of the field by explaining the theory of magnetism, describing techniques to synthesize magnetic particles, and detailing methods to characterize magnetic particles. The second section describes biomedical applications, including chemical sensors and cellular actuators, and diagnostic applications such as drug delivery, hyperthermia cancer treatment, and magnetic resonance imaging contrast"--
Foreword / Urs Hafeli -- Introduction to biomedical applications of magnetic nanoparticles / Jeffrey N. Anker and Thompson Mefford -- Magnetic particle fundamentals. A conceptual introduction to the fundamentals of magnetic fields, magnetic materials, and magnetic particles for biomedical applications / Timothy G. St. Pierre -- Magnetic forces and torques : separation, tweezing, and materials assembly in biology / Benjamin Yellen -- Colloidal interactions of magnetic nanoparticles / O. Thompson Mefford and Steven L. Saville -- Magnetic characterization : instruments and methods / Cindi L. Dennis -- Magnetic particle applications. Synthesis and functionalization of magnetic particles / Erika C. Vreeland and Dale L. Huber -- Nanomagnetic actuation : controlling cell behavior with magnetic nanoparticles / Jon Dobson and Sarah H. Cartmell -- Magnetic nanoparticles : challenges and opportunities in drug delivery / Allan E. David, Mahaveer S. Bhojani, Adam J. Cole -- Magnetic particle biosensors / Yunzi Li, Paivo Kinnunen, Alexander Hrin, Mark A. Burns, and Raoul Kopelman -- Magnetic contrast imaging : magnetic nanoparticles as probes in living systems / Robert C. Woodward, Matthew R.J. Carroll, Micheal J. House, and Timothy G. St. Pierre -- Energy dissipation by magnetic nanoparticles : basic principles for biomedical applications / Mythreyi Unni and Carlos Rinaldi -- Toxicology of magnetic nanoparticles / Stephen J. Klaine, Jordan T. Burbage, Paul W. Millhouse, Unaiza Uzair, and Jeffrey N. Anker.
OCLC-licensed vendor bibliographic record.
Keywords: Magnetic materials; Biomedical engineering; Nanobiotechnology; Nanoparticles; TECHNOLOGY / Material Science; SCIENCE / Life Sciences / Biophysics